PENGARUH PEMBERIAN ART THERAPY TERHADAP SELF ESTEEM PADA PASIEN ANAK DENGAN LEUKEMIA DI RUMAH SAKIT - isnaini - rahmawati (LPPMK STIKES Widyagama Husada, 2019)
Leukimia is one of the dangerous cancer among children between 0 to 18 years old. Cancer is one of the etiology of children death. The World Health Organization (WHO) stated in 2008 that cancer is a position-determining disease in the world after cardiovascular disease. One of the treatments for leukemia is chemotherapy. The effects of chemotherapy include nausea, vomiting, weakness etc. so that children's daily activities can be carried out, it is feared that there will be a decrease in self-confidence in interactions with others. Including children in therapeutic activities is one way to socialize to children, so that it is expected to increase self-esteem in children.The aim of the study : to determine the effect of art therapy on self esteem’s patient with leukimia in Dr. Moewardi Hospital. Method : this study was quasy experiment, pre and post test without control design. Result : Paired T test was used in this data analisis, the result obtained p 0,000 (p <0.05), so there is an effect of art therapy on self esteem’s patient with leukimia in Dr. Moewardi Hospital. Conclusion : art therapy increases the self esteem’s patient with leukimia in Dr. Moeardi Hospital.